Power Output of Spring-Mounted Lifting Plates in Axial Flow - Howell, Richard; Lucey, Anthony (Springer, 2016)
In this paper, two different spring-mounting systems of lifting flexible plates in ideal flow are compared for their suitability in energy harvesting of induced flutter instability via the reciprocating motion of the spring system. In previous work, it was found that compared to a fixed cantilever the introduction of the dynamic support in both systems yields lower flutter-onset flow speeds which is desirable for energy harvesting applications. The first system is a cantilevered thin flexible plate aligned with a uniform flow with the upstream end of the plate attached to a spring-mass system. We compare this system to one where the upstream end is hinged with a rotational spring at the mount. We map out the linear stability and power output characteristics of both systems with the introduction of dashpot damping at the mount. As expected the introduction of damping stabilises both systems and the order of magnitude of this stabilisation varies non-linearly for different levels of damping; this results in optimal points for energy harvesting for each system.